Coordinated Metabolic Changes and Modulation of Autophagy during Myogenesis - Fortini, Paola (Front Physiol, 2016)
Autophagy undergoes a fine tuning during tissue differentiation and organ remodeling in order to meet the dynamic changes in the metabolic needs. While the involvement of autophagy in the homeostasis of mature muscle tissues has been intensively studied, no study has so far addressed the regulation of autophagy in relation to the metabolic state during the myogenic differentiation. In our recently published study (Fortini et al., 2016) we investigated the metabolic profile and regulation of autophagy that accompany the differentiation process of mouse skeletal muscle satellite cells (MSC)-derived myoblasts into myotubes. Here, we briefly present these findings also in the light of similar studies conducted by other authors. We show that during myogenic differentiation mitochondrial function and activity are greatly increased, and the activation of autophagy accompanies the transition from myoblasts to myotube. Autophagy is mTORC1 inactivation-independent and, remarkably, is required to allow the myocyte fusion process, as shown by impaired cell fusion when the autophagic flux is inhibited either by genetic or drug manipulation. Further, we found that myoblasts derived from p53 null mice show defective terminal differentiation into myotubes and reduced activation of basal autophagy. Of note, glycolysis prevails and mitochondrial biogenesis is strongly impaired in p53-null myoblasts. Thus, autophagy, mitochondrial homeostasis, and differentiation are finely tuned in a coordinate manner during muscle biogenesis.